2022
DOI: 10.1002/pro.4395
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of SARS‐CoV‐2 nsp10–nsp16 in complex with small molecule inhibitors, SS148 and WZ16

Abstract: SARS‐CoV‐2 nsp10–nsp16 complex is a 2′‐O‐methyltransferase (MTase) involved in viral RNA capping, enabling the virus to evade the immune system in humans. It has been considered a valuable target in the discovery of antiviral therapeutics, as the RNA cap formation is crucial for viral propagation. Through cross‐screening of the inhibitors that we previously reported for SARS‐CoV‐2 nsp14 MTase activity against nsp10–nsp16 complex, we identified two compounds (SS148 and WZ16) that also inhibited nsp16 MTase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The interactions identified in this study were previously reported, which confirms that the LTE-expressed proteins were functional, and the assay could efficiently detect their interactions. For instance, the crystal structure of the NSP10-NSP16 complex involved in viral RNA capping has been revealed earlier, and this complex formation is required to activate the 2′- O -methyltrasferase function of the NSP16 protein. , In our assay, the alpha signal intensity obtained for this complex was 5 × 10 4 CPS, which was 25× higher than the background signal.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The interactions identified in this study were previously reported, which confirms that the LTE-expressed proteins were functional, and the assay could efficiently detect their interactions. For instance, the crystal structure of the NSP10-NSP16 complex involved in viral RNA capping has been revealed earlier, and this complex formation is required to activate the 2′- O -methyltrasferase function of the NSP16 protein. , In our assay, the alpha signal intensity obtained for this complex was 5 × 10 4 CPS, which was 25× higher than the background signal.…”
Section: Resultssupporting
confidence: 84%
“…29−33 For instance, the crystal structure of the NSP10-NSP16 complex involved in viral RNA capping has been revealed earlier, and this complex formation is required to activate the 2′-O-methyltrasferase function of the NSP16 protein. 34,35 In our assay, the alpha signal intensity obtained for this complex was 5 × 10 4 CPS, which was 25× higher than the background signal.…”
Section: Expression Of the Sars-cov-2 Proteome In The Ltementioning
confidence: 56%
“…In fact, only a handful of inhibitors of viral MTases, mostly targeting flaviviruses 26,27 , were known prior to the COVID-19 pandemic. However, recently many inhibitors of SARS-CoV-2 MTases were reported by us and others 19,[28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…These targets are well-precedented in antiviral research, with successful drugs treating analogous enzymes for HIV, HCV, RSV, HBV, HCMV, HSV, HPV, and human influenza virus, among others, and these SARS-CoV-2 enzymes have been the focus of enormous efforts among many groups. ,,, Other SARS-CoV-2 enzymes have attracted less attention, likely because there is less precedence for their targeting as antivirals. Nevertheless, enzymes like the macrodomain , and the papain-like protease of Nsp3, and the MTases Nsp10–Nsp16 complex and Nsp14 play key roles in the virulence of SARS-CoV-2. While they have little precedence as antiviral drug targets, they seem attractive as novel enzymes for antiviral drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5,10−13 Other SARS-CoV-2 enzymes have attracted less attention, likely because there is less precedence for their targeting as antivirals. Nevertheless, enzymes like the macrodomain 14,15 and the papain-like protease of Nsp3, 16 and the MTases Nsp10− Nsp16 complex 17 and Nsp14 play key roles in the virulence of SARS-CoV-2. 18−21 While they have little precedence as antiviral drug targets, they seem attractive as novel enzymes for antiviral drug discovery.…”
Section: ■ Introductionmentioning
confidence: 99%